PENERAPAN METODE PEMBELAJARAN DISKUSI DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKn DI SMA SWASTA KAMPUS TELUKDALAM KELAS XI MIA-B - Arliman Gari (Universitas Nias Raya, 2023)
This study is motivated by low student learning outcomes. This study aims to determine the improvement of student learning outcomes through the application of learning methods discussion on subjects PPKn Class XI MIA-B Private High School campus Telukdalam. The research method used is a qualitative research method with the type of research is Class Action Research (PTK). The subjects of this study were students of Class XI MIA-B Private High School Kampus Teluk dalam Tahun Pelajaran 2021/2022. Research object class XI MIA-B with the number of 23 people. The findings of the study using the learning method of discussion showed that the results of processing the value of learning outcomes in the first cycle obtained by 56.52% while the processing of the value of learning outcomes in the second cycle of 86.95%. It can be concluded that the discussion learning method is an effective learning method to improve student learning outcomes. Because the discussion learning method makes students more active in the teaching and learning process. Suggestions offered by researchers, discussion learning methods should be used as an alternative in learning because it can improve student learning outcomes more actively and effectively.